Factors Affecting the Incidence of Placental Retention in Pregnant - Annur Dian Elviana; Faizah Betty Rahayuningsih (Indonesian Journal of Global Health Research, 2025)
Placental retention is a critical medical condition where the placenta fails to exit the uterus after childbirth, potentially causing severe bleeding and maternal death. It is identified when the placenta remains inside the uterus 30 minutes after delivery. This study examines factors influencing placental retention at Dr. Moewardi Regional General Hospital, Surakarta. Using a quantitative case-control design, this study compared 200 medical records: 100 with placental retention and 100 without, using a simple random sampling technique. Inclusion criteria were medical records from 2021 to 2024 detailing maternal age, parity, childbirth history, delivery type, uterine contractions, abortion history, and education, while incomplete records were excluded. The analysis of the data was conducted using the chi-square test, applying a significance threshold set at p less than 0.05. Results revealed significant relationships between childbirth history (p=0.000), delivery type (p=0.000), uterine contractions (p=0.000), and placental retention. However, maternal age (p=0.499), parity (p=1.000), abortion history (p=0.078), and education (p=0.091) showed no significant associations. These findings can guide future research using different methodologies.